"And Thence from Jerusalems Ruins": Romantic Prophecy and the End(s) of History. Issue 11 (4th November 2013) - Bundock, Christopher
Abstract: Several comprehensive and influential studies of Romanticism in the 1950s, 60s and 70s paid special attention to the role of prophecy as an aesthetic and psychological framework for reading the major Romantic poets – Keats, Byron and Coleridge but especially Wordsworth, Shelley and Blake. One of the goals of this paper is to suggest that this interest, perhaps now seen as somewhat dated, is not so much past as sublated in several more contemporary studies. As recent work illustrates, prophecy remains a vital phenomenon for reading Romanticism, though realizing its full potential means imagining the concept anew. Once rethought, prophecy offers a productive focus for reconsidering the interrelation of major topics in Romanticism including the imagination, representation, subjectivity, performativity and history – all of which are touched on below. This topic is particularly important today when prevailing attitudes toward the future seem divided between either a fascination with the non‐future of apocalyptic annihilation – whether natural or supernatural – or the perpetuation of history's "end" in neoliberal capitalism, an opposition Fredric Jameson expresses as the strange fact that today "it is easier to imagine the end of the world than the end of capitalism" (199). The hope here is that a review of Romantic prophecy may inspire more varied and creative responses to contemporary thought about what is and is not possible for art and history. What follows is a kind of biography of the philosophical life of prophecy that takes account of how the concept is serially revised as it is assimilated by different literary‐critical movements from approximately the 1950s to the present day. This is not to say that there is a simply linear development in the thinking of the phenomenon; rather, and most interestingly, different notions of prophecy overlap with each other, producing a palimpsest indicating multiple, simultaneous levels of significance. Nor is this paper a comprehensive catalogue of critical work on Romantic prophecy – this would require much more time. Rather, it attempts to sketch out some of the most important and interesting directions scholarship on this topic has taken over the past few decades.